Cytostatic in vitro Effects of DTCM-Glutarimide on Bladder Carcinoma Cells - Brassesco, Maria S. (2012)
Bladder cancer is a common malignancy worldwide. Despite the increased use of cisplatin-based combination therapy, the outcomes for patients with advanced disease remain poor. Recently, altered activation of the PI3K/Akt/mTOR pathway has been associated with reduced patient survival and advanced stage of bladder cancer, making its upstream or downstream components attractive targets for therapeutic intervention. In the present study, we showed that treatment with DTCM-glutaramide, a piperidine that targets PDK1, results in reduced proliferation, diminished cell migration and G1 arrest in 5637 and T24 bladder carcinoma cells. Conversely, no apoptosis, necrosis or autophagy were detected after treatment, suggesting that reduced cell numbers in vitro are a result of diminished proliferation rather than cell death. Furthermore previous exposure to 10 mu g/ml DTCM-glutarimide sensitized both cell lines to ionizing radiation. Although more studies are needed to corroborate our findings, our results indicate that PDK1 may be useful as a therapeutic target to prevent progression and abnormal tissue dissemination of urothelial carcinomas.